The development of reservation system for Permai Cat Cottage / Fathiah Afiqah Mohd Dusuki - Mohd Dusuki, Fathiah Afiqah (2017)
Permai Cat Cottage is a business related to cat. Permai Cat Cottage providing varieties of services such as boarding, grooming, cat’s supply and cat studio. The data regarding customers, cats and reservations need to be recorded to ensure there is no redundancy of data. This cat’s cottage always interact with the customer’s details and reservation is recorded by the admin herself. The details are recorded in a paper based and keep in a folder. The development of this project will assist the admin and customers of Permai Cat Cottage in managing their customer’s details and reservation’s details in their daily operation. This project is carried out with the aim to develop web-based reservation system for Permai Cat Cottage. This project are using the waterfall model and three-tier architecture model. The waterfall model involving requirement gathering and analyse the requirement, design phase and implementation phase. As the result, Reservation System for Permai Cat Cottage is produced together with documentations of Software Requirement Specification (SRS) and Software Design Documentation (SDD). For the future work, the development of this system can be extended more for the testing phase of System Sequence Diagram.